Comparison of Patriotism Values based on the Existence of Superhero Films: Comparative Study of Indonesia and America - Hakiki, Elfira Amalia; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to compare the value of Patriotism in Indonesian and American superhero films. Methodology: This study adopts a qualitative approach with a content analysis design to conduct a comparative analysis. The primary data for this research is obtained through the observation of films available on streaming platforms such as Netflix and Disney+. The data collection technique involves viewing films on these platforms. The analysis techniques employed in this research encompass three main stages: (1) data reduction, (2) data presentation, and (3) drawing conclusions or verification. Results: The research findings indicate similarities and differences in portraying patriotism in Indonesian and American superhero films. Similarities include emphasising values such as love for the country, courage, perseverance, and readiness to make sacrifices for the greater good. However, differences emerge in how patriotism is expressed: Indonesian superheroes often demonstrate pride in cultural heritage, while American counterparts typically exhibit pride in national symbols. Moreover, Indonesian superheroes showcase patriotism through actions, whereas American superheroes convey it through words and actions. It is also noted that American superhero films may sometimes present a form of false patriotism, which could potentially harm the country and its citizens. Overall, the study suggests that both Indonesian and American superhero films effectively promote patriotism due to the presence of patriotic elements within their narratives. Applications/Originality/Value: The research findings reveal similarities and differences in the depiction of patriotism in Indonesian and American superhero films.